Baccharoides lasiopus: Review of its Medicinal uses, Phytochemistry and Pharmacological Properties - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2020)
Baccharoides lasiopus is a woody shrub widely used as traditional medicine throughout its distributional range in tropical Africa. This study is aimed at providing a critical review of the pharmacological properties, phytochemistry, and medicinal uses of B. lasiopus. Documented information on the pharmacological properties, phytochemistry, and medicinal uses of B. lasiopus was collected from several online sources, which included Scopus, Google Scholar, PubMed and Science, and pre-electronic sources such as book chapters, books, journal articles and scientific publications obtained from the university library. The articles published between 1971 and 2020 were used in this study. This study showed that the leaves, roots, stems, whole plant parts, root and stem bark of B. lasiopus are widely used as galactagogue, purgative and anthelmintic, and traditional medicine for headache, liver diseases, skin diseases, respiratory infections, malaria, augment labour, convulsions, epilepsy, fainting, female reproductive problems, and gastro-intestinal problems. Phytochemical compounds identified from the species include elemanolide type sesquiterpene lactones, alkaloids, anthraquinones, cardiac glycosides, coumarins, flavonoids, phenolics, reducing sugars, saponins, steroids, tannins, terpenoids, and xanthines. Pharmacological research revealed that B. lasiopus extracts and compounds isolated from the species have anthelmintic, antibacterial, antifungal, antiviral, antihyperglycemic, antiplasmodial, antimalarial, antiprotozoal, haematological, hepatoprotective, hepatotoxicity, larvicidal, and cytotoxicity activities. Future research on B. lasiopus should focus on the possible biochemical mechanisms of action of both the crude extracts and identified phytochemical compounds including toxicological, in vivo, and clinical studies to corroborate the traditional medical applications of the species.